Morfologi Thalus Lichen di Kawasan Jalur Pendakian Bukit Mongkrang Kecamatan Tawangmangu Kabupaten Karanganyar - Efri Roziaty; Khurotul Agyuni (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Lichen is an association of fungi and algae, morphologically and physiologically unified as a single entity. Lichen is categorized as plants characterized by a thallus-like form. The aim of this research was to investigate the thallus morphology of lichens along the hiking trails of Bukit Mongkrang, Tawangmangu District, Karanganyar Regency, Central Java Province. The research utilized an exploratory method involving exploration of locations to obtain necessary samples. Purposive sampling was employed to select research locations comprising three stations at varying altitudes. Subsequently, lichen morphology samples were identified. The results revealed three types of thalli: Crustose, Foliose, and Fruticose, with Foliose being the most dominant type at 335 individuals, and Crustose the least at 132 individuals. The most dominant surface morphology of lichen thalli was Maculae details in the species Polyblastidium albicans (Pers.) S.Y. Kondr, Lokos & Hur, while the least common surface detail was Cephalodia in the species Lepraria casiella R.C. Harris. Lichen reproductive structures identified included two types: sexual and asexual. Sexual reproductive structures consisted of Apothecia, Perithecia, and Pycnidia, while asexual reproductive structures included Isidia and Soredia. The most dominant sexual reproductive structure found was Apothecia in the species Lecanora glabrata (Ach.) Malme, and the least common was Pycnidia in the species Anaptychia palmulata (Michaux) Vain. Morphological differences among lichen types were influenced by variations in altitude, air temperature, humidity, and light intensity. Lichen was most abundant at elevations ranging from 1,712 to 1,844 meters above sea level.